Decision Support System for Selection of Virtual Reality Head-Mounted Display Using the WASPAS Method - Nurhasan Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Virtual reality is a technology that allows one to carry out simulations by presenting three-dimensional visuals and atmosphere through a device called a Head-Mounted Display (HMD) or VR HMD. To make a VR HMD selection, users must know one by one the specifications of the product to be selected, this of course makes the selection process long and makes it difficult to make a choice. This study aims to develop a decision support system by implementing the Weighted Aggregated Sum Product Assessment (WASPAS) approach for selecting VR HMDs, in order to make it easier for users to make decisions. The WASPAS method can determine the best alternative through prioritization that is relevant to the weighting used. Based on the case study conducted, the best alternative results were Shinecon 6.0 VR Box with a value of 0.9021, followed by Enric VR Box with a value of 0.8965, Yoko VR Box with a value of 0.8179, VRPark VR Box with a value of 0.8158 and BoboVR Z5 VR Box with a value of 0.7827. The built decision support system has produced valid calculations, this is because the calculations obtained by the system with manual calculations produce the same value. On the results of usability testing get an average value of 90% and fall into the good category. This shows that the developed system is easy to use and feasible to implement.